Sclerosing mesenteritis presenting as acute abdominal emergency - Turkalj, Ivan; Petreš, Andrej; Vanhoenacker, Filip; Petrović, Kosta; Stojanović, Sanja; Spasić, Aleksandar; Popović, Dušan; Mikov, Ivan (PONS - medicinski časopis, 2015)
Sclerosing mesenteritis (SM) is a rare and poorly understood chronic benign inflammatory condition of the mesentery that sometimes can be manifested as acute abdominal emergency. We report a case of a 62-year-old man who was diagnosed SM on computed tomography (CT) which was confirmed histopathologically. SM manifests grossly as a diffuse, localized, or multinodular thickening of the mesentery. Microscopically, according to the pattern of the disease, SM can be divided into sclerosing panniculitis where necrosis and inflammation predominate and retractile mesenteritis in which fibrosis and retraction are hallmarks of the disease.  Clinical presentation of patients suffering from SM is quite diverse - from asymptomatic, which is the most common, to abdominal pain, bloating, nausea, vomiting and febrile episodes. The ‘fat ring sign’ and peripheral pseudocapsule are virtually pathognomonic CT findings of SM. Management of SM is empirical with no guidelines yet established. SM should be listed in the differential diagnosis in every older patient with diverse abdominal complaints.